2014
DOI: 10.17851/2237-2083.22.1.67-93
|View full text |Cite
|
Sign up to set email alerts
|

Referenciação e técnicas experimentais: aspectos metodológicos na investigação do processamento correferencial em português brasileiro

Abstract: ResumoNeste artigo, discutimos algumas questões metodológicas envolvidas na realização de experimentos psicolinguísticos, com ênfase em métodos on-line de experimentação, no paradigma de leitura autocadenciada e em estudos sobre referenciação. Apresentamos, também, resultados de dois experimentos de leitura autocadenciada sobre o processamento correferencial, em português brasileiro, de nomes repetidos, pronomes plenos e pronomes nulos, tanto em retomada de antecedentes em posição de sujeito quanto de objeto. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…In fact, the corpus analysis conducted by Duarte (1990) showed that the passive represents 4.7% of finite verb forms in written language, whereas Guimarães and Souza (2016) reported passives to represent 0.8% of finite verb forms in oral language. The written task has also affected the study conducted by Maia and Cunha Lima (2014). The authors failed to observe tendencies in spoken language reflected on written tasks: in their study of coreference in BP, their initial experimental items showed subject pronouns in object position, which, while more frequent than the grammatically prescribed clitics in oral BP, increased reaction times and caused noise in their data for being exhibited in written form.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, the corpus analysis conducted by Duarte (1990) showed that the passive represents 4.7% of finite verb forms in written language, whereas Guimarães and Souza (2016) reported passives to represent 0.8% of finite verb forms in oral language. The written task has also affected the study conducted by Maia and Cunha Lima (2014). The authors failed to observe tendencies in spoken language reflected on written tasks: in their study of coreference in BP, their initial experimental items showed subject pronouns in object position, which, while more frequent than the grammatically prescribed clitics in oral BP, increased reaction times and caused noise in their data for being exhibited in written form.…”
Section: Discussionmentioning
confidence: 98%
“…Não houve diferença significativa entre as duas estruturas com pronomes clíticos (β=-0,5135, p<0,403), mas o pronome clítico em ênclise, nosso nível de referência, foi significativamente mais aceito que o pronome tônico (β=-0,2028, p<0,001). A percepção dos pronomes clíticos como mais aceitáveis que os pronomes tônicos estão de acordo com nossa hipótese e com os estudos anteriores sobre o tema (MAIA; LIMA, 2014;OLIVEIRA et al, no prelo). No entanto, esperávamos que os pronomes clíticos em próclise seriam percebidos como mais aceitáveis que os pronomes clíticos em ênclise, como em Oliveira et al (no prelo).…”
Section: Percepção E Aceitabilidade Dos Pronomes Clíticosunclassified
“…O processamento de hiperônimos também é facilitado em relação ao de hipônimos no português brasileiro em adultos saudáveis (13) . E há resultados divergentes na Penalidade do Nome Repetido em Português Brasileiro, em pesquisas com adultos sem patologias, alguns estudos têm encontrado sistematicamente a ocorrência do fenômeno, com pronomes sendo processados mais rapidamente do que nomes repetidos, tanto na posição de sujeito, quanto na posição de objeto (3,(13)(14)(15)(16) , entretanto há estudos que não têm encontrado tais diferenças (17)(18)(19)(20) .…”
Section: Introductionunclassified